Investigation of in vitro effects of fluoride on bovine sperm - Tanyildizi, S; Bozkurt, T (Scientific Technical Research Council Turkey, 2002)
The in vitro effects of various concentrations Of sodium fluoride on the percentages of motile spermatoza and abnormal spermatozoa with the hyaluronidase activities of semen were investigated. Holstein bulls (n=20), aged between 4 and 5 years, were used in this study. The semen samples obtained from all animals were divided into five parts and one of them was used as the control sample. Sodium fluoride solutions were prepared at concentrations of 30, 60, 120 and 240 mM and then these solutions were mixed 1:1 with semen samples to determine semen hyaluronidase activity, sperm motility and morphological abnormality of spermatozoa at 5, 10, 15, 20 and 30 minutes. The semen hyaluronidase activities and the percentages of abnormal spermatozoa were determined to increase highly significantly (p<0.001) in comparison with control samples at all times. However, significant (p<0.001) decreases were established in the percentages of sperm motility. In addition, significant negative correlations (p<0.001) were determined between the hyaluronidase activities and sperm motilities of all groups at all times, after the incubation of sodium fluoride with sperm samples. In conclusion, these results indicated that when sodium fluoride was applied in vitro to bovine sperm, it caused toxic effects. Furthermore, there were significant relationships between hyaluronidase activity and sperm motility.
Keywords: hyaluronidase; sperm; motility; bull